PENGARUH PERMAINAN TRADISIONAL TERHADAP HASIL BELAJAR LARI JARAK PENDEK SISWA SMP NEGERI 7 KOTA SUKABUMI - Vingkan Ayu Aryati (Universitas Negeri Medan, 2019)
This study aims to determine the results of learning to run short distances through traditional game treatments at SMP Negeri 7 Sukabumi City in the academic year 2019/2020. This type of research used in this study is an experiment. The design in this study was one group pretest-posttest. The sample technique used in this research is purposive technique. The sample in this study amounted to 27 students. The instrument used was the test and measurement of short distance running, which is to find out the results of learning to run short distances. The data analysis technique used is the test for normality, homogeneity and hypothesis testing (t-test). Based on research and data analysis, there is an influence of traditional games on the results of learning to run short distances in class VIII students at SMP Negeri 7, Sukabumi City. This is evidenced by the t-test of 5,045> t-table (2,060) at the real level (∝) 0.05. Thus, Ho is accepted and Ha is rejected. The conclusion of this study is